TRANSLATION OF PHRAZEOLOGICAL UNITS FROM ENGLISH INTO UZBEK LANGUAGE - Abduvaxobova Maftuna Vohid qizi (Modern American Journals, 2025)
This article examines the importance of linguistic and semantic features of phraseological units in the process of translation. In addition, the correct use of English phraseological units in the Uzbek context and the problems faced by translators are analyzed.
Keywords: Phraseology, stable combinations, standard, metaphor, methods, culture, translation difficulties.